Relationship between body mass index and family functioning, family communication, family type and parenting style among African migrant parents and children in Victoria, Australia: a parent-child dyad study - S. Cyril; J. Halliday; J. Green; A.M.N. Renzaho (BMC, 2016)
Abstract Background Although childhood obesity prevalence is stabilised in developed countries including Australia, it is continuing to rise among migrants and socially disadvantaged groups in these countries. African migrants and refugees in particular, are at high risk of obesity due to changes in their family dynamics. The aim of this study was to examine the difference between children and parental perception of family functioning, family communication, family type and parenting styles and their relationship with body mass index. Methods A cross-sectional parent-child dyad study was conducted among 284 African families from migrant and refugee backgrounds living in metropolitan Melbourne, Australia. Bilingual workers were trained to collect demographic, anthropometric and questionnaire data on family functioning, parenting, family type and family communication. Results Parents and children reported different levels of family dynamics. Children reported a higher prevalence of poor family functioning (61.5 %, 95 % CI: 55.6, 67.2 versus 56.8 %, 95 % CI: 49.7, 61.6) and protective family type (29 %, 95 % CI: 23.9, 34.5 vs. 13.4 %, 95 % CI: 9.9, 17.9), but a lower prevalence of authoritative parenting style (51.6 %, 95 % CI: 45.7, 57.5 vs. 63 %, 95 % CI: 57.5, 68.8) than parents. There was a positive relationship between poor family functioning and child BMI both before (β = 1.28; 95 % CI: 0.14, 2.41; p < 0.05) and after (β = 1.73; 95 % CI: 0.53, 2.94; p < 0.001) controlling for confounders, and an inverse relationship between consensual family type and child BMI after adjustment (β = −1.92; 95 % CI: −3.59, −0.24; p < 0.05). There was no significant relationship between parental BMI and family functioning, communication, family type or parenting style. Conclusion Children's perception of poor family functioning was associated with childhood obesity. Family interventions to reduce childhood obesity need to adopt an intergenerational approach to promote a clear understanding of family dynamics between children and parents. Unless these intergenerational challenges associated with family dynamics are clearly addressed in obesity interventions, current obesity prevention initiatives will continue to widen the childhood obesity gap in Australia.